ANALISIS STRUKTUR RANGKA MESIN VACUM FORMING MENGGUNAKAN FINITE ELEMENT ANALYSIS - Jamil, Farur; Asrofi, Muhammad; Sidartawan, Robertus; Triono, Agus; Sholahudin, Imam; Kristianta, FX; Nurdiansyah, Haidzar (Jurusan Teknik Mesin, 2023)
The SME sector is the source of all aspects related to the pattern of human life, starting from the clothing, food and housing sectors. In the process of forming the packaging there are several methods used, the method that is often used is thermoforming. One of the simplest thermoforming methods is vacuum forming. In this research, research will be carried out to identify the strength of the frame structure of a vacuum forming machine with ST 37 iron material. This research focuses on vacuum forming machine frames. The weight of each component includes a 5.2 Kg Box Heater, 7.2 Kg Vacuum Chamber and 3.2 Kg Vacuum. The results obtained from this study are that the vacuum forming machine frame is able to withstand other machine frames. Where the results of the simulation and analytical calculations are not much different. Visualization of the loading of the vacuum forming machine can be seen immediately where the location of the critical load during the simulation is the Maximum Normal Stress of 1.1689 Mpa. The Minimum Normal Stress is -0.88281 and the shear stress is 0.3865 Mpa. And for the safety factor of this simulation is 31.44. The frame of the vacuum forming machine holds the load of the entire component.